Eliminating the need for routine monthly postdialysis serum urea nitrogen measurement: A method for monitoring Kt/V and normalized protein catabolic rate using conductivity determined dialyzer clearance. Issue 6 (11th October 2018) - Daugirdas, John T.
Abstract: Many dialysis machines can compute dialyzer sodium clearances at multiple time points during a dialysis treatment using conductivity. For a given treatment, the average dialyzer sodium clearance (K), when combined with treatment time (t), and the estimated urea distribution volume (V, usually based on either anthropometry or bioimpedance), can be used to estimate Kt/V, an important measure of hemodialysis adequacy. While this conductivity‐derived value for Kt/V correlates moderately with Kt/V calculated from predialysis and postdialysis serum urea nitrogen (SUN) values (urea reduction ratio, URR), the ultrafiltration volume, and session length it is, unfortunately, not sufficiently accurate to replace URR‐based Kt/V. Here we underline the potential utility of an alternative method to estimate Kt/V (a variant of a technique originally proposed by Gotch and Levin and their colleagues) using conductivity‐derived sodium clearance (K) that does not require routine measurement of the postdialysis SUN but which should closely track Kt/V computed in the usual fashion. The increased accuracy with the new method is explained by the use of a patient‐specific value of V, which is an average value calculated from several dialysis sessions where both conductivity dialyzer clearance and predialysis and postdialysis SUN have been measured. Once this patient‐specific conductivity/URR‐based value for V has been determined, it can be used to calculate Kt/V for subsequent treatments in which conductivity‐based dialyzer clearances are measured, but around which predialysis and postdialysis SUN values have not been obtained. (If the predialysis SUN values for such a subsequent treatment are also measured, then a normalized protein catabolic rate that closely tracks the value from conventional urea modeling, can also be determined.) By reducing the number of postdialysis SUN measurements needed to monitor hemodialysis adequacy this new method of estimating Kt/V by conductivity should save staff time and laboratory costs, increase patient and staff safety, and decrease error rates associated with improper postdialysis blood sampling technique.